1999
DOI: 10.1002/hep.510300428
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and the development of ammonia-induced brain edema in rats after portacaval anastomosis

Abstract: Two mechanisms may account for brain edema in fulminant hepatic failure: the osmotic effects of brain glutamine, a product of ammonia detoxification, and a change of cerebral blood flow (CBF). We have shown brain edema, a marked increase in brain glutamine, and a selective rise in CBF in rats after portacaval anastomosis receiving an ammonia infusion. In this study, we inhibited the activity of glutamine synthetase with methionine-sulfoximine (MSO) and examined ammonia levels, brain water and CBF. A major comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(94 citation statements)
references
References 30 publications
5
87
2
Order By: Relevance
“…It has been shown that pre-treatment of cultured astrocytes with the irreversible GS inhibitor, methionine sulfoximine (MSO), result in an attenuation in the increase in ammonia-induced glutamine and swelling (Norenberg and Bender, 1994). Similar results have been observed following ammonia-infusion in portacaval shunted rats pre-treated with MSO (Master et al, 1999 andWillard-Mack et al, 1996). However, following ammonia-lowering treatments, which are beneficial in attenuating brain edema and the onset of coma in animal models of ALF, a decrease in high cerebral glutamine levels was not observed Zwingmann et al, 2004).…”
Section: Glutamine/glutamatementioning
confidence: 60%
“…It has been shown that pre-treatment of cultured astrocytes with the irreversible GS inhibitor, methionine sulfoximine (MSO), result in an attenuation in the increase in ammonia-induced glutamine and swelling (Norenberg and Bender, 1994). Similar results have been observed following ammonia-infusion in portacaval shunted rats pre-treated with MSO (Master et al, 1999 andWillard-Mack et al, 1996). However, following ammonia-lowering treatments, which are beneficial in attenuating brain edema and the onset of coma in animal models of ALF, a decrease in high cerebral glutamine levels was not observed Zwingmann et al, 2004).…”
Section: Glutamine/glutamatementioning
confidence: 60%
“…Studies in portacaval shunted rats administered an ammonia load have demonstrated a rise in CBF that paralleled the increase in ICP and correlated directly with brain water content. 25,26 Cerebral hyperemia is of crucial importance in the development of increased ICP in ALF. Normal cerebral vascular resistance is essential for the maintenance of cerebral autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive vasodilatation or vasoconstriction ensures constant cerebral perfusion. 27 When methods are introduced to control the rise in CBF, such as methionine-sulfoximine (an inhibitor of glutamine synthase) 25 and mild hypothermia, 28 ammonia-induced cerebral edema is prevented. It also has been shown that the cerebral vasoconstrictor indomethacin blunts the rise in CBF in portacaval shunted rats receiving an ammonia load and that the consequent reduction in CBF leads to a disproportionate reduction of ammonia uptake by the brain, which may reduce brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In vivo studies have shown that administration of methionine sulfoximine (MSO), which specifically inhibits GS, ameliorates astrocyte swelling and brain edema observed during acute hyperammonemia. [10][11][12][13] A decreased ammonia fixation by GS may lead either to a stimulation of an alternative ammoniascavenging pathway or to a corresponding, increased ammonia concentration. A study using neuronal-astrocytic co-cultures provided evidence for a high incorporation of ammonia nitrogen in both alanine and glutamine, 14 suggesting that ammonia might be metabolized not only via GS catalyzed formation of glutamine but also by the concerted action of glutamate dehydrogenase (GDH) and alanine aminotransferase (ALAT) leading to trapping of ammonia in alanine, as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%